Informing agricultural sectoral inputs for the update of the National Determined Contribution of Colombia through its Climate Change Plan for Agricultural Sector (PIGCCS)). - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
EC-LEDS research outputs produced by CCAFS and CIAT informed the Climate Change Plan for Agricultural Sector (PIGCCS-Ag) of Colombia, which was the policy instrument used to update Colombia's NDC.